Created Mother For Able Technology And To Protect Children From Sexual Abuse With The "Hai Dia" Application: Wujudkan Ibu Cakap Teknologi Dan Pelindung Anak Dari Bahaya Kekerasan Seksual Dengan Aplikasi “Hai Dia” - Saleha, Nurmukaromatis; Sardaniah; Nurlailli; Aprilatutini, Titin (Procedia of Social Sciences and Humanities, 2022)
The development of the industry towards the 5.0 era and triggered by the Covid-19 pandemic made the use of online media rampant. Many parents are aware of the dangers of online media for children, but the lack of mastery of technology is an obstacle for parents in protecting their children. This activity aimed to increase the knowledge of mothers in protecting their children from the risk of sexual violence both by contact and online through the mobile-based application “Hi Dia”. The method used was the community education method through counseling. The educational materials provided were the socialization of the underwear rules, parenting materials on Online Gender-Based abuse, and technology lecture materials for mothers. Twenty-five mothers participated offline in this activity. Mothers' knowledge about protecting children from the dangers of online sexual abuse was measured before and after the paired t-test was carried out. The results obtained p-value 0.005 concluded that there was an increase in the knowledge of mothers in protecting their children from the dangers of sexual abuse. This activity should be made a routine agenda considering the rapid development of technology triggers the need for technology-savvy mothers to protect their children from the dangers of online media.